Lightning detection on Venus: a critical review - Ralph D. Lorenz (Progress in Earth and Planetary Science, 2018)
Abstract Claimed detections and nondetections of lightning and related electromagnetic emissions on Venus are qualitatively contradictory. Here, motivated by the commencement of observations by the Akatsuki spacecraft and by studies of future missions, we critically review spacecraft and ground-based observations of the past 40 years, in an attempt to reconcile the discordant reports with a minimal number of assumptions. These include invoking alternative interpretations of individual reports, guided by sensitivity thresholds, controls, and other objective benchmarks of observation integrity. The most compelling evidence is in fact the first, the very low frequency (VLF) radio emissions recorded beneath the clouds by all four of the Veneras 11–13 landers, and those data are re-examined closely, finding power-law amplitude characteristics and substantial differences between the different profiles. It is concluded that some kind of frequent electrical activity is supported by the preponderance of observations, but optical emissions are not consistent with terrestrial levels of activity. Venus’ activity may, like Earth’s, have strong temporal and/or spatial variability, which coupled with the relatively short accumulated observation time for optical measurements, can lead to qualitative discrepancies between observation reports. We note a number of previously unconsidered observations and outline some considerations for future observations.